PENGARUH KARAKTERISTIK WIRAUSAHA, ORIENTASI PEMBELAJARAN DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA (Studi Pada Usaha Kecil Pengolahan Pangan Di Kota Palembang) - Jusmawi Bustan (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
This study aims to determine the effect of the characteristics of entrepreneurs, learning orientation and entrepreneurial orientation on business success. The study population is  small entrepreneurs in the food processing sector in Palembang consist of  19.457 businesses. By using a precision level of 10%, the sample size is 100 people. The sampling technique used in this research is purposive sampling. Data were analyzed using multiple regression approach with SPSS 19. The results showed that the characteristics of entrepreneurs, learning orientation, entrepreneurial orientation have significant effect on business success. There is no linear relationship between the characteristics of the entrepreneurial and business success. There is a linear relationship between learning orientation and business success. There is a linear relationship between entrepreneurial orientation and business success. Results of research can be developed into a strategy for small entrepreneurs in the food processing in Palembang to increase the success of efforts undertaken.